Recharging Difficulty With Pulse Generator After Deep Brain Stimulation: A Case Series of Five Patients - Li, Hongyang; Su, Daoqing; Lai, Yijie; Xu, Xinmeng; Zhang, Chencheng; Sun, Bomin; Li, Dianyou; Pan, Yixin (Frontiers in Neuroscience, 2021)
Background: Deep brain stimulation (DBS) is a well-established treatment for a variety of movement disorders. Rechargeable cell technology was introduced to pulse generator more than 10 years ago and brought great benefits to patients. However, with the widespread use of rechargeable implanted pulse generators (r-IPGs), a new hardware complication, when charging the r-IPG has been difficult, was encountered. Objective: The aims of this study were to report five cases confronted with r-IPG charging difficulty postoperatively and to explore the predisposing factors and treatment strategies for this rare complication. Methods: We retrospectively reviewed our DBS patient database for those who were implanted with r-IPGs. From 2012, we identified a total of 1,226 patients, with five of them experiencing charging difficulties after surgery. Detailed patient profiles and clinical procedures were scrutinized and reviewed. Results: All the charging problems were resolved by reoperation. Cases 1 and 2 required their r-IPGs to be anchored to the muscle and fascia. Cases 3 and 4 had their r-IPGs inserted in the wrong orientation at the initial surgery, which was resolved by turning around the r-IPGs at the revision surgery. Case 5, in which we propose that the thick subcutaneous fat layer blocked the connection between the r-IPG and the recharger, required a second operation to reposition the r-IPG in a shallow layer underneath the skin. For all cases, the charging problems were resolved without reoccurrences to date. Conclusion: Our case series indicates a novel hardware complication of DBS surgery, which had been rarely reported before. In this preliminary study, we describe several underlying causes of this complication and treatment methods.